Particles in ambient air — a health risk assessment - Areskoug, Hans; Camner, Per; Dahlén, Sven-Erik; Låstbom, Lena; Nyberg, Fredrik; Pershagen, Göran; Sydbom, Anita (Scandinavian Journal of Work, Environment & Health, 2000)
This criteria document on particles in ambient air has been prepared at the Institute of Environmental Medicine, Karolinska Institutet, at the request of the Swedish Environmental Protection Agency. Although each chapter has main authors, the work has been a joint effort, and all conclusions and recommendations have been thoroughly discussed by the group. Besides the authors, the group included Carl-Elis Boström and Titus Kyrklund from the Swedish Environmental Protection Agency. Furthermore, a draft of the document was discussed with a reference group including Bertil Forsberg, Hans-Christen Hansson, Thomas Sandström, and Katarina Victorin. The main focus of the document is on effects other than cancer since particles in the ambient air were recently evaluated as a risk factor for cancer by the Institute of Environmental Medicine. In general, literature published through 1998 is reviewed, with occasional inclusion of important work published thereafter. However, the chapter on epidemiologic studies was prepared earlier and primarily relates to reports published through 1997.
Keywords: ambient air; ambient athmosphere; ambient particulate air pollution; diesel exhaust emission; epidemiologic study; health effect; health risk assessment; health risk evaluation; human experimental study; human lung; inhaled particles; ultrafine particle